2014
DOI: 10.1080/00087114.2014.891701
|View full text |Cite
|
Sign up to set email alerts
|

Karyological and genome size insights into cardoon (Cynara cardunculusL., Asteraceae) in Tunisia

Abstract: This study contributes the first genome size data for wild populations of Cynara cardunculus, the presumed progenitor of artichoke and cultivated cardoon. C-values estimated by flow cytometry are 2C = 1.98-2.14(3.03) pg for wild cardoon (10 populations), 2C = 2.10-2.11 pg for cultivated cardoon (two accessions) and 2C = 2.05 pg for artichoke (one accession). Chromosome counting (carried out for all material except the artichoke) establishes diploidy in all accessions. In order to provide a phylogenetic framewo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 23 publications
0
4
1
Order By: Relevance
“…The genomes size measured in this study for leafy cardoon (2C = 2.20 pg) and globe artichoke (2C = 2.40 pg) are slightly different to those previously reported by Khaldi et al (2014) and Marie and Brown (1993), respectively. Khaldi et al (2014) reported a range of variability in DNA content, from 2C = 1.98 to 3.03 pg, in 10 populations of wild cardoon, and 2C = 2.05 and 2.10-2.11 pg for a single variety of globe artichoke and for two varieties of cultivated cardoon, respectively, while Marie and Brown (1993) stated a DNA content of 2C = 2.22 pg for globe artichoke.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The genomes size measured in this study for leafy cardoon (2C = 2.20 pg) and globe artichoke (2C = 2.40 pg) are slightly different to those previously reported by Khaldi et al (2014) and Marie and Brown (1993), respectively. Khaldi et al (2014) reported a range of variability in DNA content, from 2C = 1.98 to 3.03 pg, in 10 populations of wild cardoon, and 2C = 2.05 and 2.10-2.11 pg for a single variety of globe artichoke and for two varieties of cultivated cardoon, respectively, while Marie and Brown (1993) stated a DNA content of 2C = 2.22 pg for globe artichoke.…”
Section: Discussioncontrasting
confidence: 99%
“…Khaldi et al (2014) reported a range of variability in DNA content, from 2C = 1.98 to 3.03 pg, in 10 populations of wild cardoon, and 2C = 2.05 and 2.10-2.11 pg for a single variety of globe artichoke and for two varieties of cultivated cardoon, respectively, while Marie and Brown (1993) stated a DNA content of 2C = 2.22 pg for globe artichoke. The differences between our estimates in DNA content and those of Marie and Brown (1993) and Khaldi et al (2014) can be attributed to the DNA content estimation for the internal standard ( Pisum sativum ). Both works used 2C = 8.37 pg, while we employed 2C = 9.09 pg from Doležel et al (1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This evolutionary scenario is supported by molecular analyses that indicate close relationships between the artichoke and the wild cardoon from the Eastern Mediterranean, whereas cultivated cardoons are similar to the Western wild cardoons (Sonnante, Carluccio, et al 2007;Sonnante et al 2008). Despite such progress in the evolutionary field, the cytogenetic knowledge of C. cardunculus is still scarce, being limited to the chromosome number and little basic information on the chromosome morphology of artichoke (Giorgi et al 2013;Khaldi et al 2014). Molecular cytogenetic techniques, such as FISH (fluorescent in situ hybridization), which are known to be extremely valuable tools for investigating species with small chromosomes, have not been so far applied in C. cardunculus.…”
Section: Fluorescent In Situ Hybridization (Fish)mentioning
confidence: 96%
“…Despite its relevance, the chromosome number is only known for around 25% of angiosperms (Stuessy 2009). The Asteraceae are one of the families in which major efforts towards chromosome number and genome size determination have been made (Watanabe et al 2007;Semple and Watanabe 2009;Meng et al 2012;Mousavi et al 2013;Olanj et al 2013;Khaldi et al 2014). In particular, hypotheses on basic chromosome numbers in Asteraceae have been hampered by a lack of understanding of which genera were basal within tribes and which tribes were basal within the family.…”
Section: Introductionmentioning
confidence: 99%